Pengaruh Model Pembelajaran Kooperatif Tipe Think, Talk, Write (TTW) yang Dipadu dengan Media Buku Komik Biologi terhadap Hasil Belajar Siswa SMA - Andrea Ramadhani Maharlika; Slamet Santosa; Baskoro Adi Prayitno (Universitas Sebelas Maret, 2018)
This study aims to find out the model of cooperative learningtype think, talk, write (TTW) combined with comic books result of high school student learning. This research is a quasi experiment research with Posttest-Only Nonequivalent Control Group Design. Population in this research is all student of class XI SMA Negeri 2 Sukoharjo Lesson Year 2017/2018. The selected sample is class XI MIPA 1, XI MIPA 2, and XI MIPA 4 with sampling cluster sampling technique. Data analysis using ANOVA test assisted by SPSS 24 program. Further Tukey and Least Significance Different (LSD) test to determine the effect of the best treatment. The results showed that cooperative learning model of type think, talk, write (TTW) combined with comic book media result of high school student learning.